Integrative Approach to the Professional Preparation of the Future Economists- International Affairs Experts - Maksymchuk, Larysa (Pedagogical Discourse, 2013)
The article explores the essence of integrative approach to training future international economists. The possibilities of improving the curriculum of humanities toward their professional area. Presented algorithm design classes for professional-oriented education of future professionals of foreign sphere. Examples of the use of interactive technologies in the study of psychological and educational courses to form important professional qualities of future international economists.